Pasta, pretty please : a vibrant approach to handmade noodles - Nicholson, Linda Miller; Wright, Brittany (New York : William Morrow, an imprint of HarperCollinsPublishers, 2018)
The pasta ninja and Instagram star Linda Miller Nicholson delivers her first cookbook, a stunning cornucopia of pasta in every color and shape, all created by hand using all-natural colors from vegetables, herbs, and superfoods--and including 25 dough recipes, 33 traditional and modern shaping techniques, and the perfect fillings and sauces to make your creations sing!
Dough -- Basic pasta sheeting techniques -- Advanced pasta sheeting techniques -- Gnocchi and other rolled pasta -- Sauces -- Fillings.
Includes index.
Includes bibliographical references and index.
Keywords: Cooking (Pasta); COOKING / Specific Ingredients / Pasta; COOKING / Courses & Dishes / General; COOKING / Specific Ingredients / Natural Foods; Nonfiction; Cooking (Pasta); Cookbooks; Cookbooks